White men's talk about gender-based violence in South Africa: A thematic narrative analysis of the stories told about race, class, and gender - Pitcher, Sorrel (Department of Psychology, 2024)
Gender-based violence (GBV) research in South Africa has been critiqued for producing and perpetuating trauma-saturated narratives that situate gendered violence in poor black individuals, families, and communities (Boonzaier, 2017, 2018; Boonzaier et al., 2020). Young, black, working class men, in particular, have come to be conflated with sexual violence, while white, financially privileged men remain noticeably absent from the literature (Buiten & Naidoo, 2016). In this way, research about GBV in South Africa has become implicitly racialized (Buiten & Naidoo, 2020). As a response to this gap, and with the intention of disrupting racialised knowledge production about GBV, this dissertation explores and critically analyses white men's narratives about GBV in South Africa. This study was theoretically guided by decolonial feminist theory and narrative theory, and a combination of purposive and snowball sampling via social media was utilised to recruit participants. In total, 12 semi-structured, in-depth interviews were conducted with white South African men. The individual interviews were analysed using a thematic narrative lens. Three dominant thematic narrative groupings emerged from the data: Narratives of gendered violence, masculinity narratives, and narratives of men's trauma. The narratives speak to how white men position themselves in relation to gendered violence in South Africa and the raced and classed distancing tactics that they employ to achieve this. This analysis provides a more nuanced and detailed understanding of how narratives of race, class, and gender interact with understandings of GBV. Such information could inform future GBV prevention and intervention work by highlighting novel areas of focus.